2016
DOI: 10.1038/srep26664
|View full text |Cite
|
Sign up to set email alerts
|

The protein PprI provides protection against radiation injury in human and mouse cells

Abstract: Severe acute radiation injuries are both very lethal and exceptionally difficult to treat. Though the radioresistant bacterium D. radiodurans was first characterized in 1956, genes and proteins key to its radioprotection have not yet to be applied in radiation injury therapy for humans. In this work, we express the D. radiodurans protein PprI in Pichia pastoris yeast cells transfected with the designed vector plasmid pHBM905A-pprI. We then treat human umbilical endothelial vein cells and BALB/c mouse cells wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Impressively, the enhanced role of IrrE not only expands to other microorganisms, such as Escherichia coli, , Pseudomonas putida, P. aeruginosa, , Zymomonas mobilis, Lactococcus lactis, Saccharomyces cerevisiae, , but even in Brassica napus , and mammalian cells. By in vitro random mutagenesis and in vivo selection, various IrrE variants have been obtained, which gave E. coli , or S.…”
Section: Introductionmentioning
confidence: 99%
“…Impressively, the enhanced role of IrrE not only expands to other microorganisms, such as Escherichia coli, , Pseudomonas putida, P. aeruginosa, , Zymomonas mobilis, Lactococcus lactis, Saccharomyces cerevisiae, , but even in Brassica napus , and mammalian cells. By in vitro random mutagenesis and in vivo selection, various IrrE variants have been obtained, which gave E. coli , or S.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is an unmet need to develop therapeutic agent against radiation enteropathy with good biocompatibility and efficacy. 6063 Amifostine is an FDA-approved radioprotector used in clinical settings during radiotherapy. However, its short half-life in patients limits its efficacy and extensive clinical use.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed that several certain proteins were able to function as protectors against radiation damage. 680–682 Long et al designed phytohemagglutinin (PHA-L) protein NPs to activate toll-like receptor 5 (TLR5) for radioprotection. 683 Due to spontaneous biocompatibility, the PHA-L protein NPs showed no significant cytotoxicity to CHO-K1 cells at a concentration of 100 μg mL −1 .…”
Section: Feature Application Of Precision Radiotherapy For Radioprote...mentioning
confidence: 99%